Réflexion sur la procédure de médiation de l’acte uniforme de l’OHADA relatif à la Médiation (AUM) - Adjita, Shamsidine Akrawati (Revue Internationale de Droit et Science Politique, 2025)
La médiation n’est pas une invention du législateur de l’OHADA. Elle est aussi vieille que le monde. Sa consécration légale à travers l’Acte uniforme relatif à la médiation met en évidence son importance dans la résolution des litiges à l’amiable dans l’ordonnancement juridique de l’OHADA. Cela s’explique car la médiation renvoie à l’idée de justice. Le sentiment de justice n’est pas lié à une époque, il est plutôt inhérent à l’existence humaine et porte en lui-même une exigence, une valeur fondamentale universellement reconnue. Il s’agit du droit à la justice dont le respect permet d’apprécier de façon efficiente les valeurs auxquelles une société est attachée. Toute société a besoin de justice, mais elle ne peut la rendre de façon satisfaisante avec le procédé traditionnel qu’est le jugement. Le juge ne peut pas tout. Le bon sens dicte de l’éviter. Selon un adage populaire, « un mauvais accord vaut mieux qu’un bon procès ». Là où il y a une société, il y a des différends. Là où il y a des différends, il y a des modes de règlement des différends parmi lesquels la médiation occupe une place de choix. Avatar médiatisé de la justice consensuelle, panacée de la déjudiciarisation et de la déjuridicisation, la médiation est parée de toutes les vertus pour éviter le procès. Elle apparaît donc comme une alternative à laquelle peuvent recourir les parties en conflit pour régler leur malentendu à l’amiable tout en préservant leurs relations d’affaires. Elle n’est pas une procédure laissée à l’appréciation du juge, mais plutôt à celle des parties en conflit qui en sont les principales actrices. Cependant elles ne peuvent parvenir à la résolution de leur litige que par l’intermédiaire d’un tiers appelée médiateur et sans lequel la procédure serait incomplète. On a donc, d’un côté, les parties à la médiation qui la considèrent comme étant leur affaire et, de l’autre, le médiateur qui est considéré comme le chef d’orchestre de la procédure. Mediation is not an invention of the OHADA legislator. It is as old as the world itself. Its legal recognition through the Uniform Act on Mediation highlights its importance in the amicable resolution of disputes within the OHADA legal system. This is because mediation refers to the idea of justice. The sense of justice is not tied to a particular era; rather, it is inherent to human existence and carries with it a requirement, a universally recognized fundamental value. It is the right to justice, respect for which allows for the efficient appreciation of the values to which a society is attached. Every society needs justice, but it cannot deliver it satisfactorily through the traditional process of judgment. Judges cannot do everything. Common sense dictates that it should be avoided. According to a popular saying, “a bad agreement is better than a good trial.” Where there is society, there are disputes. Where there are disputes, there are ways of resolving them, among which mediation occupies a prominent place. As the media-friendly face of consensual justice and the panacea for reducing court cases and legal proceedings, mediation is seen as the ideal way to avoid litigation. It therefore appears to be an alternative that parties in conflict can use to settle their differences amicably while preserving their business relationships. It is not a procedure left to the discretion of the judge, but rather to that of the parties in conflict, who are the main actors. However, they can only resolve their dispute through a third party called a mediator, without whom the procedure would be incomplete. On the one hand, therefore, we have the parties to the mediation, who consider it to be their business, and on the other, the mediator, who is considered to be the conductor of the procedure.
Keywords: Acte uniforme; Judge; Juge; Mediation; Mediator; Médiateur; Médiation; Parties en conflit; Parties to the dispute; Uniform Act

La contribution de la technologie vers une modernisation efficace des modes alternatifs de règlement de conflits - Sangare, Abou Bakary (Université de Montréal, 2025)
Les modes alternatifs de règlement de conflits ont révolutionné le monde du règlement de litiges grâce à leurs nombreux avantages. Les coûts moins onéreux en dehors de l’arbitrage, la célérité des procédures, la confidentialité, le dialogue ouvert, l’émergence de solutions créatives profitant plus ou moins à chacune des parties, constituent entre autres les nombreux éléments qui les rendent plus efficaces par rapport à une procédure contentieuse devant une instance judiciaire ordinaire. Cependant, ces modes alternatifs de règlement de conflits font quand même face à bien d’écueils qui les rendent au fil du temps moins efficaces. L’imprévisibilité des situations conflictuelles apportées à la table des instances de résolution, entraîne une inadéquation des solutions envisagées. De plus, le capital humain fait aussi défaut quand on sait que le nombre de ces règlements amiables de litiges de ces dernières années accroît considérablement, acculant ainsi le personnel de gestion de ces conflits qui se retrouve à faire face aux mêmes défis que le personnel des instances judiciaires contentieuses. De plus, l’humain ne pouvant se détacher indéfiniment de ses émotions peut très rapidement tomber dans la partialité quand il s’agit de prendre des décisions. Il est dès lors capital de penser à une modernisation de ces modes alternatifs de règlement de conflits afin de les rendre plus efficaces par le biais de nouveaux moyens technologiques. Certes, la Résolution de litiges en ligne existe depuis quelques années maintenant. Cependant, il est temps d’y apporter de nouveaux ingrédients afin de rendre meilleure la recette. Alternative dispute resolution has revolutionized the world of dispute resolution thanks to its many advantages. Lower costs, faster procedures, confidentiality, open dialogue and the emergence of creative solutions that benefit both parties to a greater or lesser extent - these are just some of the factors that make alternative dispute resolution more effective than litigation in the ordinary courts. However, these alternative dispute resolution methods do face a number of pitfalls that make them less effective over time. The unpredictability of conflict situations brought to the resolution table leads to inadequate solutions. What's more, human capital is also in short supply, as the number of out-of-court settlements in recent years has risen sharply, leaving conflict management staff facing the same challenges as staff in contentious legal proceedings. What's more, since human beings are unable to detach themselves from their emotions indefinitely, they can quickly fall into the trap of bias when it comes to making decisions. It is therefore vital to consider modernizing these alternative dispute resolution methods, in order to make them more effective through new technological means. Online dispute resolution has been around for some years now. However, it's time to add new ingredients to make the recipe even better.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitration; Blockchain; Chatbots; Conciliation; ICT; Internet; Justice; Justice prédictive; MARD; Mediation; Modes alternatifs de règlement de conflits; Médiation; Négociation; ODR; Online dispute resolution; Predictive justice; Règlement de litiges en ligne; TIC; Technologie; Technology; Transaction

L'équilibre de la relation entre investisseur étranger et État hôte dans la jurisprudence arbitrale - Jorland, Maxime (Université Paris-Saclay, 2025)
Le droit des investissements internationaux s'est construit sous l'impulsion des tribunaux arbitraux qui, dans leur rôle d'interprétation du droit international coutumier et des traités d'investissement, ont contribué à enrichir le droit matériel des investissements. La multiplication des sentences rendues a constitué progressivement une véritable jurisprudence, visant à équilibrer la relation entre l'investisseur étranger et l'État hôte. Cependant, l'interprétation des traités par les tribunaux arbitraux s'est souvent faite dans un objectif de protection de l'investisseur face à la puissance publique de l'État, jusqu'à inverser parfois le rapport de force entre les deux opérateurs. De plus, l'absence de principe de précédent en arbitrage d'investissement a contribué à créer un flou notionnel, du fait des interprétations changeantes des dispositions des traités protégeant l'investisseur étranger. 2Cette étude vise donc à faire état du droit positif des investissements internationaux en déterminant un courant doctrinal commun aux sentences arbitrales. Une fois ce travail de compilation réalisé, l'objectif sera alors de déterminer l'état de l'équilibre des forces entre les deux opérateurs et proposer un rééquilibrage du droit des investissements. Ce rééquilibrage passe notamment par une redéfinition des critères jurisprudentiels imprécis ou changeants et une adaptation de la protection de l'investisseur étranger aux enjeux modernes du commerce international, tout en veillant à permettre à l'Etat hôte de conserver ses prérogatives de puissance publique. International investment law has largely been shaped by arbitral tribunals, whose interpretative function with regard to customary international law and investment treaties has contributed significantly to the development of substantive investment law. The proliferation of arbitral awards has progressively given rise to a de facto jurisprudence, aimed at striking a balance between the interests of foreign investors and the sovereign rights of host States. However, treaty interpretation by arbitral tribunals has often been guided by a protective logic in favour of the investor, at times to the extent of inverting the power dynamic between the two actors. Furthermore, the absence of a binding precedent doctrine in investment arbitration has fostered conceptual uncertainty, resulting from fluctuating interpretations of the treaty provisions safeguarding foreign investors.This study seeks to provide an overview of the current state of positive international investment law by identifying a coherent doctrinal trend emerging from arbitral case law. Based on this synthesis, the aim is to evaluate the prevailing balance of power between the investor and the host State, and to propose avenues for rebalancing investment law. Such rebalancing entails, in particular, a clarification of vague or inconsistent jurisprudential standards and an adaptation of investor protection to contemporary challenges of international trade, while ensuring that host States retain their sovereign regulatory authority.
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; CIRDI; Etat hôte; FDI; Host state; ICSID; International; Investissements; Investissements étrangers; Investisseur; Investments; Investor

La revalorisation des mécanismes locaux de prévention et de gestion des conflits au Mali : une valeur ajoutée inestimable pour le système judiciaire moderne - Yalcouyé, Seydou; Dolo, Anidjou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La cohabitation entre les mécanismes modernes et traditionnels de prévention et de gestion des conflits au Mali (notamment dans en milieu rural) est une réalité. Entre les mécanismes modernes et les mécanismes traditionnels, le choix des communautés porte essentiellement sur les seconds ; quoique les premiers ne sont pas non plus en abandon. Comme raisons avancées pour justifier leur choix, elles considèrent de façon générale que le recours aux mécanismes modernes ne permet pas de vider totalement leur contentieux. Les communautés trouvent que ces mécanismes modernes rendent leurs conflits plus complexes et plus difficiles à gérer. D’où la méfiance du règlement administratif ou judiciaire des conflits car trop couteux et aux procédures trop complexes. Sur la base de ces constats, il reste permis de constater la nécessité de réaliser des compromis entre mécanismes modernes et mécanismes traditionnels de gestion des conflits en revalorisant davantage les seconds. Seul à ce prix que les défis de la décentralisation (gouvernance locale) et ceux de la démocratie seront relevés. The coexistence of modern and traditional conflict prevention and management mechanisms in Mali (particularly in rural areas) is a reality. Compared to modern and traditional mechanisms, communities primarily choose the latter; although they have not abandoned the former either. As reasons given to justify their choice, they generally consider that resorting to modern mechanisms does not completely resolve their disputes. Communities find that these modern mechanisms make their conflicts more complex and more difficult to manage. Hence their distrust of administrative or judicial conflict resolution, as they are too costly and require overly complex procedures. Based on these observations, it remains clear that compromises must be made between modern and traditional conflict management mechanisms by further revaluing the latter. Only in this way will the challenges of decentralization (local governance) and democracy be met.
Keywords: Autorité traditionnelle; Conflict management; Conflict prevention; Gestion des conflits; Gouvernance locale; Local governance; Légitimité traditionnelle; Prévention des conflits; Traditional authorities; Traditional legitimacy

The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

Analyse critique du développement de la médiation en France : les résistances à l'essor de la médiation en droit privé - Prêté, Safya Bayoub (Université Bourgogne Franche-Comté, 2025)
La médiation est une technique de communication faisant intervenir un tiers impartial, neutre et indépendant, pour aider des individus à trouver une issue à leur crise conflictuelle. Par essence, la médiation est un outil de résolution des conflits pacifiant, fondé sur la responsabilisation des parties. Attrayante par sa souplesse, louée pour son coût présenté comme modéré, le législateur en a encouragé l’expansion. Alors que l’article 21 du code de procédure civile confie au juge la mission de concilier les parties, la médiation devient l’un des outils privilégiés par les pouvoirs publics pour permettre la réalisation de cette mission. Ainsi, la loi n°95-125 du 8 février 1995, relative à l’organisation des juridictions et à la procédure civile, pénale et administrative, institue la médiation judiciaire. Elle marque le début d’un ancrage législatif en faveur de ce processus. Ce premier mouvement en faveur de la médiation s’est accéléré en France, à l’initiative de l’Union européenne qui a fait adopter le 21 mai 2008 la Directive 2008/52/CE portant sur la médiation en matière civile et commerciale. Le postulat de départ de ce texte est qu’un « cadre juridique prévisible peut permettre aux citoyens de l’Union européenne (UE) de bénéficier pleinement des avantages de la médiation en tant que mécanisme de résolution des conflits, notamment sur le plan de la rentabilité et de la rapidité ». Puis, la médiation conventionnelle a été encadrée au sein du code de procédure civile. L’intégration de la Directive 2008/52/CE au sein du corpus de normes du droit interne positif a permis de créer une définition légale de la médiation en ces termes : « La médiation régie par le présent chapitre s'entend de tout processus structuré, quelle qu'en soit la dénomination, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l'aide d'un tiers, le médiateur, choisi par elles ou désigné, avec leur accord, par le juge saisi du litige ».Or, le mouvement d’expansion de la médiation semble freiné par un jeu de résistances. Certaines de ces résistances concernent le processus et sont prévisibles. D’autres tiennent à des variables exogènes, résultats de questionnements sur la médiation, le médiateur, l’office du juge, la déjudiciarisation, la déjuridictionnalisation, et l’ordre public. L’étude pose que l’essor de la médiation est contrarié par une méconnaissance de la médiation, ainsi qu’en raison d’une méconnaissance des acteurs de la médiation.Le mouvement d’encouragement des pouvoirs publics à la tentative de médiation, pour prévenir ou traiter des contentieux du droit privé, semble se muer en une politique globale de l’amiable, recentrée sur la mission du juge de concilier les parties. Cette politique de l’amiable persiste à produire des normes tendant, notamment, à encadrer la médiation, à créer un statut pour le médiateur, dans l’optique d’acculturer les justiciables à ce mode amiable.L’objet de la présente thèse est d’analyser les résistances à l’essor de la médiation en droit privé et leurs conséquences sur son développement en France. Il s’agit de saisir ces résistances et leurs enjeux ; et de redonner force au processus de médiation, en offrant à ses prescripteurs un faisceau d’arguments intelligibles. Mediation is a communication technique involving an impartial, neutral and independent third party to help individuals find a way out of their conflict crisis. By nature, mediation is a pacifying conflict resolution tool, based on the accountability of the parties. Attractive for its flexibility, praised for its moderate cost, the legislator encouraged its expansion. While Article 21 of the Code of Civil Procedure entrusts the judge with the task of reconciling the parties, mediation is becoming one of the tools favoured by the public authorities to enable this mission to be carried out. Thus, Law No. 95-125 of February 8, 1995, relating to the organization of the courts and civil, criminal and administrative procedure, establishes judicial mediation. It marks the beginning of a legislative anchoring in favour of this process. This initial movement in favour of mediation has accelerated in France, at the initiative of the European Union, which adopted Directive 2008/52/EC on mediation in civil and commercial matters on May 21, 2008. The premise of this text is that "a predictable legal framework can allow citizens of the European Union (EU) to fully benefit from the advantages of mediation as a dispute resolution mechanism, particularly in terms of cost-effectiveness and speed". Then, conventional mediation was framed in the Code of Civil Procedure. The incorporation of Directive 2008/52/EC into the body of norms of positive domestic law has made it possible to create a legal definition of mediation in the following terms: "Mediation governed by this chapter means any structured process, whatever its name, by which two or more parties attempt to reach an agreement with a view to the amicable resolution of their disputes, with the help of a third party, the mediator, chosen by them or appointed, with their agreement, by the judge hearing the dispute". However, the movement towards the expansion of mediation seems to be slowed down by a game of resistance. Some of these resistances are process-related and predictable. Others relate to exogenous variables, the result of questions about mediation, the mediator, the judge's office, diversion, dejurisdictionalization, and public order. The study posits that the development of mediation is thwarted by a lack of knowledge of mediation, as well as because of a lack of knowledge of the actors involved in mediation. The movement to encourage the public authorities to attempt mediation, to prevent or deal with private law disputes, seems to be turning into a global policy of amicable litigation, refocused on the judge's mission to reconcile the parties. This amicable policy persists in producing standards tending, in particular, to regulate mediation, to create a status for the mediator, with a view to acculturating litigants to this amicable method. The purpose of this thesis is to analyze the resistance to the rise of mediation in private law and their consequences on its development in France. It is a question of grasping these resistances and their stakes; and to give strength to the mediation process, by offering its prescribers a bundle of intelligible arguments.
Keywords: Amiable; Arbitrage (droit); Arbitration; Civil Law; Contract Law; Contrats; Droit civil; Droit des contrats; Droit privé; France; Mediation; Médiation; Private Law; Procedure Law; Procédure civile; Settlment

El arbitraje como justicia alternativa y eficaz - Nieto, Gastón Fabricio Correa (Polo del Conocimiento, 2025)
El presente ensayo surge de la experiencia del ejercicio profesional de la abogacía en la que en el ámbito judicial, extrajudicial, donde se ha observado diferentes vicisitudes en el desarrollo y ejecución de procesos judiciales, generando de esta forma ineficiencia en la administración de justicia; para lo cual como alternativa viable surgen los métodos alternativos de solución de conflictos con la promulgación de la Ley de Arbitraje y Mediación surgen en septiembre de 1997 como una opción ante la deficiente administración de Justicia.Sin embargo, esta ineficiencia procesal representa a su vez un obstáculo real para su ejercicio efectivo de derechos, especialmente obtener “justicia” para los ciudadanos que enfrentan demoras prolongadas y procedimientos burocráticos que terminan por vulnerar sus derechos. Uno de los objetivos del artículo es la de establecer las medidas efectivas que se pueden adoptar en instancia extrajudicial y elementos necesarios alcanzar la tan preciada “Justicia” siendo esta “la constante y perpetua voluntad de dar a cada quien lo que le corresponde” (Ulpiano, 2015).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Deficiencia judicial; Justicia; Negligencia; Retardo

Comercio sostenible y arbitraje internacional: un enlace estratégico para la resolución de conflictos - León, Jorge Guillermo Cedeño; Erazo, Angie Gabriela Sánchez (Polo del Conocimiento, 2025)
El arbitraje internacional ha emergido como una herramienta clave para la resolución de controversias en el comercio sostenible, ofreciendo un marco eficiente y flexible. Este estudio analiza el uso del arbitraje en casos relacionados con comercio y sostenibilidad, evaluando su efectividad en la promoción de prácticas comerciales responsables.
Keywords: Arbitrage international; Arbitraje internacional; Comercio sostenible; Commerce durable; International commercial arbitration; Prácticas responsables; Resolución de controversias; Sostenibilidad

Impacto de las tecnologías emergentes en la confidencialidad y transparencia del arbitraje internacional - Pérez-Pacheco, Yaritza; Lee, Díckar Bonyuet (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
El arbitraje comercial internacional enfrenta el desafío de integrar tecnologías emergentes como la inteligencia artificial, el Big Data y el blockchain, sin comprometer sus principios fundamentales de confidencialidad y transparencia. Este artículo analiza, a partir de una revisión documental y comparativa, cómo el uso de estas tecnologías im-pacta la gestión de casos, el análisis predictivo y la ejecución de laudos, al tiempo que mejora la eficiencia y accesibilidad del arbitraje, pero también genera riesgos en materia de privacidad, ciberseguridad y protección de datos sensibles. Asimismo, se analizan los enfoques regulatorios adoptados en distintas jurisdicciones, incluyendo el Reglamento de la Unión Europea, el modelo flexible de Estados Unidos y las iniciativas tecnológi-cas de países asiáticos como China y Hong Kong. La investigación concluye que, para equilibrar la innovación y la protección de la información, es indispensable implementar protocolos globales y estándares éticos que garanticen un arbitraje confiable y seguro en entornos digitales. International commercial arbitration faces the challenge of integrating technologies such as artificial intelligence, Big Data, and blockchain, without undermining confidentiality and transparency. This article examines how these tools impact case management, predictive analysis, and the enforcement of awards, improving efficiency while also raising concerns about privacy and cybersecurity. Regulatory approaches are explored, from the European Union’s framework to the more flexible model of the United States and technological initiatives in Asia. The research concludes that it is essential to establish global and ethical standards to ensure a secure and reliable arbitration process in the digital era.
Keywords: Arbitrage; Arbitragem; Arbitraje internacional; Arbitral award enforcement; Arbitration; Confidentiality; Confidentialité; Ejecución de laudos arbitrales; Emerging technologies; International arbitration; International dispute resolution; Resolución internacional de disputas; Tecnologías emergentes; Transparence; Transparency

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

La transparencia en el arbitraje internacional: avances y nuevos retos - Pollero, Marianela Bruno (Jurídica Ibero: Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
Este artículo responde a la propuesta académica del Departamento de Derecho de la Uni-versidad Iberoamericana en conmemoración del 10.° aniversario de las normas de trans-parencia de la Comisión de las Naciones Unidas para el Derecho Mercantil (CNUDMI) y complementa la actividad académica realizada por la Universidad Iberoamericana, la Secretaría de Relaciones Exteriores de México y el Centro de Mediación y Arbitraje de la Cámara de Comercio de la Ciudad de México (CANACO), con el apoyo de la Secre-taría de la CNUDMI, en el marco del UNCITRAL LAC DAYS- México 2024. Durante esta actividad se organizaron tres mesas de debate integradas por desta-cados miembros de la comunidad arbitral, de la sociedad civil y del sector privado. La temática de estudio brindó desde México una visión sobre la confidencialidad vs. la transparencia, así como los avances y los retos de la transparencia en el arbitraje inter-nacional.
Keywords: Arbitrage international; Arbitragem Internacional; Arbitraje internacional; Arbitration; Transparence (droit); Transparencia

Reflexiones sobre el régimen de transparencia en el arbitraje comercial internacional - Rendón, Martha Angélica Alvarez (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
From an approach to the concepts of transparency, confidentiality, and privacy, this article examines the tension that may arise between these principles in international commercial arbitration. It also analyzes how arbitration rules address confidentiality and transparency, questioning whether a balance between the two has been achieved. Additionally, it reflects on the impact of public interest in promoting transparency in arbitral proceedings, considering whether the measures adopted are compatible with this type of arbitration. Desde un acercamiento a las nociones de transparencia, confidencialidad y privacidad, en este artículo se valora la tensión que puede existir entre dichos conceptos en el arbi-traje comercial internacional. Asimismo, se alude a algunos reglamentos de arbitraje que abordan la confidencialidad y la transparencia, parar mostrar si se alcanza un equilibrio entre los principios analizados. Además, se llama a reflexionar sobre el impacto del inte-rés público en la búsqueda de la transparencia en los procesos arbitrales, con la finalidad de abrir el debate sobre la compatibilidad de las medidas que se han adoptado en este rubro en el arbitraje comercial.
Keywords: Arbitrage; Arbitragem; Arbitraje comercial internacional; Arbitraje de inversión; Arbitration; Confidencialidad; Confidentiality; International commercial arbitration; Interés público; Investment arbitration; Privacidad; Privacy; Public interest; Transparence; Transparencia; Transparency

Les ADR comme mécanismes de gestion des différends sociaux et environnementaux dans les grands projets miniers au Cameroun - Abane Engolo, Patrick Edgard; Abomo Efoua, Christiane (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Les grands projets miniers sont porteurs d’enjeux économiques, sociaux, et environnementaux au Cameroun. L’exploitation minière est dans ce sens juridiquement encadrée par le Code minier. Elle implique autant d’opportunités que de risques susceptibles d’engendrer des différends sociaux et environnementaux. La gestion de ces différends implique la convocation des Alternative Dispute Resolution (ADR), qui constituent une voie d’accès à la résolution des litiges aussi importante que la saisine du juge. Cependant, l’apparente libéralité de ces ADR suscite des inquiétudes quant à l’efficacité de leur mise en œuvre et leur force juridique. Il en ressort que, bien que ces mécanismes soient consacrés, leur encadrement juridique nécessite d’être renforcé. Major mining projects pose economic, social and environmental challenges in Cameroon. Mining operations are therefore legally regulated by the Mining Code. They present both opportunities and risks that can lead to social and environmental disputes. Managing these disputes therefore requires the convening of Alternative Dispute Resolution (ADR) mechanisms, which constitute a means of accessing justice as important as going to court. However, the apparent liberality of these ADR mechanisms raises concerns about the effectiveness of their implementation and their legal force. It appears that although these mechanisms are established, their legal framework needs to be strengthened.
Keywords: Arbitrage; Arbitration; Conciliation; Mediation; Médiation; Parties prenantes; Stakeholders

L’apport du juge à l’autorité de la chose jugée de la sentence arbitrale en contentieux du sport au Cameroun - Mandeng, Naomie Audrey (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Par le truchement de la résolution des litiges nés du mouvement et des acteurs sportifs, le juge statuant dans le contentieux sportif se préoccupe également de l’applicabilité de ses décisions juridictionnelles. Sauf que l’on ne devrait pas généraliser le poids de celle-ci sur tous les cas rendus par le juge sportif. Se voulant intelligible ce dernier l’acuité de l’autorité de chose jugée face à certains incidents de procédure. Cette négation est davantage entretenue par des modalités spécifiques. Par ailleurs, dans son énoncé, le juge sportif prescrit de se référer au dispositif pour dériver prosaïquement les termes de l’autorité de chose jugée et la force exécutoire de la sentence arbitrale.
Keywords: Autorité de la chose jugée; Cameroun; Juge; Sentence arbitrale; Sport

Libres propos sur la volonté des parties dans l’arbitrage OHADA - Waham Mayegle, Joseph Laurent (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
L’arbitrage est une réalité en Afrique depuis longtemps déjà. C’est avec l’avènement de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires que ce domaine a pu avoir un dispositif bien structuré. Etant un mode alternatif de règlement des différends, l’arbitrage a pour fondement prépondérant la volonté des parties qui y font recours. Il s’est donc posé en filigrane la question de la portée de la volonté des parties à l’arbitrage OHADA. Le constat est que tout comme en matière contractuelle, elle est un élément indispensable à l’efficacité de ce mode de résolution des litiges. C’est la raison pour laquelle sa portée est traduite par une prégnance avérée, et un recul tout de même constaté.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Volonté des parties

La seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario - Muñoz, Nohely Alejandra Zambrano; Pacheco, Marco Antonio Acosta; Reyes, Eloísa Carolina Solís; Parra, José Antonio Velez (Polo del Conocimiento, 2025)
El estudio de la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario tuvo como objetivo analizar la incidencia de la seguridad jurídica en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario como garantía de los procesos judiciales. Para lo cual, se utilizó una investigación de tipo desriptiva y de campo, con un enfoque mixto y el método hermenéutico; para la recopilación de información primaria se aplicó una encuesta y entrevista a los juristas en libre ejercicio de su profesión. Se obtuvo que que todas las personas tienen derecho al debido proceso, el cual está ligado estrechamente al derecho a la seguridad jurídica ya que, este segundo implica el conocimiento y certeza del derecho positivo, la confianza de la sociedad en las instituciones del Estado y en el orden jurídico y la existencia de mecanismos jurídicos frente a las afectaciones que pudieren existir. Se concluyó que la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales es esencial para mantener la confianza en el sistema legal y para proteger los derechos fundamentales de las personas involucradas en cualquier procedimiento legal, ya sea voluntario, sumario u ordinario.
Keywords: Debido proceso; Due process; Judicial decisions; Legal certainty; Ordinary procedure; Procedimiento ordinario; Procedimiento sumario; Procedimiento voluntario; Resoluciones judiciales; Seguridad jurídica; Summary procedure; Voluntary procedure

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

L'amélioration de l'accès à la justice au Bénin dans le domaine commercial et foncier : comment les modes alternatifs de règlement des conflits et la technologie peuvent être mis à contribution ? - Agoïnon, Fifamè Danielle Esperancia (Université de Montréal, 2025)
En dépit de l'importance cruciale de la justice au sein de notre société, il est manifeste que le système judiciaire béninois présente d'importants défis en matière d'accessibilité, d'efficacité et de confiance publique. Les coûts de la justice, la perte de contrôle des problèmes, les délais d’attente avant procès, la structure labyrinthique des tribunaux, l'impossibilité de se représenter seul, ainsi que le caractère inhospitalier des tribunaux constituent des indicateurs d'un système judiciaire défaillant. En effet, des limitations dans l'accès à la justice alimentent la méfiance des citoyens à l'égard du système judiciaire étatique. Dans un souci de célérité et d'efficacité de la justice, un vent de généralisation des modes alternatifs de règlement des conflits et de recours des technologies souffle sur les procédures judiciaires en général et sur les procédures civiles et commerciales en particulier. S’inscrivant dans cette logique, la loi n° 2020-08 du 23 Avril 2020 portant modernisation de la justice en République du Bénin n’a pas manqué de faire faire une place aux modes alternatifs de règlement des conflits. Elle met également un accent sur la dématérialisation progressive des procédures judiciaires concernant la saisine des juridictions, le suivi des procédures et le paiement électronique des frais afférents. Cependant, malgré ces mesures à encourager, les juridictions, au risque de rompre, ploient toujours devant les litiges fonciers et commerciaux. La présente étude a pour objet d'analyser les forces et les faiblesses du système judicaire béninois et vérifier si la modernisation des modes alternatifs de règlement des différends et l’intégration de la technologie dans les processus de résolution des différends peuvent être un vecteur de l’accès à la justice au Bénin. Despite the crucial importance of justice in our society, it is clear that the Beninese justice system presents significant challenges in terms of accessibility, efficiency and public trust. The costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent the costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent oneself, as well as the inhospitable nature of the courts are indicators of a broken justice system. Indeed, limitations in access to justice fuel citizens' mistrust of the state justice system. In the interests of speed and efficiency of justice, a wind of generalization of alternative methods of dispute resolution and recourse of technologies is blowing through judicial procedures in general and civil and commercial procedures in particular. In line with this logic, Law No. 2020-08 of 23 April 2020 on the modernization of justice in the Republic of Benin did not fail to make room for alternative methods of conflict resolution. It also emphasizes the gradual dematerialization of judicial procedures concerning the referral of cases to the courts, the monitoring of procedures and the electronic payment of related costs. However, despite these measures to be encouraged, the courts, at the risk of breaking down, are still bending before land and commercial disputes. The purpose of this study is to analyze the strengths and weaknesses of the Beninese judicial system and to verify whether the modernization of alternative dispute resolution methods and the integration of technology into dispute resolution processes can be a vector of access to justice in Benin.
Keywords: ACCESS TO JUSTICE; ADR; Accès à la justice; Business; Bénin; Commercial; Différend; Dispute; Foncier; Information; Land; MARD; Technologie; Technology

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Global Arbitration Review, 2025)

Arbitration Fees, Expenses and Determination Controls - Al-Taani, Muhanned; Al-Majali, Tawfiq; Mosabeh, Rageh; Mayah, Yousef (Jordan Journal of Applied Science-Humanities Series, 2025)

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation, Mediation, and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation, Industrial; Officials and employees; Social justice

La mise en œuvre de la médiation institutionnelle en droit OHADA - Oueina, Florent; Oussale, Aladji Aberridjoua Aubin Hugues (Revue africaine de droit des affaires, 2025)
Il ne suffit pas d’adopter un nouvel Acte uniforme pour satisfaire à la demande ou garantir une sécurité juridique apparente du droit africain des affaires ou encore enrichir le régime uniforme du règlement des différends dans l’espace OHADA ; ou même pallier le vide législatif qui existait encore au sein de l’OHADA sur la médiation. Il ne s’agit pas d’un Acte uniforme de plus, mais d’un réel instrument juridique qui pourrait favoriser le retour des investisseurs et améliorer les conditions des affaires dans l’espace OHADA. Il faut chercher à savoir si cette nouvelle approche de la justice sera une réussite dans ledit espace.

Mediación y Arbitraje en Línea: Ventajas y Desafíos - Salguero, Katherine Coraima Guano; López, Vilma Patricia Salguero; Cáceres, Alez Remigio Escobar; Chávez, Luis Alberto Morales (Polo del Conocimiento, 2025)
La mediación y el arbitraje en línea han surgido como soluciones eficaces para la resolución de conflictos en un mundo digitalizado, ofreciendo ventajas como reducción de costos, accesibilidad y flexibilidad horaria. Sin embargo, enfrentan desafíos como la brecha digital y la seguridad de la información. Un estudio basado en encuestas a profesionales y usuarios confirma la utilidad de estas herramientas, pero subraya la necesidad de mejorar la infraestructura tecnológica y establecer marcos regulatorios claros. A pesar de los obstáculos, estos métodos representan una evolución significativa en la gestión de disputas legales.
Keywords: Arbitrage; Arbitragem; Arbitraje en línea; Arbitration; Brecha digital; Mediación; Mediation; ODR; Online dispute resolution

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

L'équité dans l'arbitrage - Djeudjo Tankeu, Ghislain (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le tribunal arbitral tranche le litige conformément aux règles de droit, mais cette garantie est fragile car le législateur OHADA ajoute à moins que les parties lui aient conféré mission de statuer en amiable composition. Ces amiables compositeurs sont donc des arbitres qui peuvent ne pas appliquer la loi, qui peuvent statuer en équité, ce qui implique la reconnaissance, aux arbitres, d’un pouvoir modérateur sur les obligations contractuelles litigieuses. Mais cette autorisation de statuer en amiable composition ne leur interdit pas de statuer en droit, simplement, le tribunal arbitral amiable compositeur qui appliquerait exclusivement les règles de droit, doit s’expliquer sur la conformité de celles-ci à l’équité. L’arbitrage tend aussi à la satisfaction de l’idéal du procès équitable. C’est ainsi que l’équité est une exigence dans la constitution et lors des suites du tribunal arbitral. The arbitral tribunal shall decide the dispute in accordance with the rules of law; but this guarantee is fragile because the OHADA legislator adds unless the parties have given him the mission to rule in amicable composition. These amicable composers are therefore arbiters who may not apply the law, who can rule in equity; which implies the recognition, to the arbitrators, of a moderating power over the disputed contractual obligations. But this authorization to rule in amicable composition does not prevent them from ruling in law. Clearly, the amicable arbitral tribunal which would exclusively apply the rules of law, must explain their compliance with fairness. Arbitration also tends to satisfy the ideal of a fair trial. This is how fairness becomes a requirement in the constitution and during the proceedings of the arbitral tribunal.

Le règlement des différends en matière d’environnement au Cameroun - Gueukam Tchako, Yannick (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
La présente contribution intitulée « Le règlement des différends en matière d’environnement au Cameroun » ; vise la mise en œuvre des règles de protection de l’environnement de par l’impact des actes mis en cause ou du préjudice causé, selon l’origine des acteurs ou selon les règles invocables. Ce faisant, elle s’intéresse aux solutions qu’apportent certaines dispositions relatives à la matière environnementale au cameroun. A l’analyse, on observe dans la première hypothèse, que les modes alternatifs de règlement non contentieux des différends se veulent plus rapide et accessibles tout en favorisant le respect des lois environnementales. Dans la seconde hypothèse, il s’agit de faire appel au juge judiciaire pour trancher les différends. De par son impact, la position du juge apparaît comme l’outil essentiel d’identification des dommages susceptibles d’être causés à l’environnement et constituant le socle sur lequel est construit le plan de gestion de l’environnement. The present contribution entiled « The settlement of environmental disputes in Cameroon » ; aims at the implementation of environmental protection rules according to the impact of the acts in question or of the damage caused, depending on the origin of the impact or according to the invocable rules. In doing so, it looks at the solutions provited by certain provisions relating to environmental matters in Cameroun. On analysis, it can be observed in the first hypothesis, the alternative methods of non-contentious settlement of disputes that are intented to be faster and more accessible while promoting compliance with environmental laws. In the second hyperthesis, it is a question of appealing to the judicial judge to settle disputes. Because of its impact, the position of the judge appears to be the essentiel tool for identifying the damage likely to be caused to the environment and constituting the basis on which the environmental management plan is built.
Keywords: Différends; Disputes; Environment; Environnement; Jurisdictional settlement; MARD; Non-jurisdictional settlement; Règlement juridctionnel; Règlement non juridictionnel

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)